Hyperbaric oxygen therapy for radiation cystitis after pelvic radiotherapy: Systematic review of the recent literature. (15th October 2019) - Villeirs, Lauren; Tailly, Thomas; Ost, Piet; Waterloos, Marjan; Decaestecker, Karel; Fonteyne, Valerie; Van Praet, Charles; Lumen, Nicolaas
Abstract: The present study assessed the efficacy of hyperbaric oxygen therapy in reducing symptoms of radiation cystitis, a specific type of iatrogenic injury to the bladder, by systematic review of recent literature. The MEDLINE, Embase and Web of Science databases were searched using combinations of the terms "radiation, " "cystitis" and "hyperbaric oxygen" to identify articles evaluating patients with radiation cystitis, treated with hyperbaric oxygen therapy. Only recent (≤10 years) original studies were included. Data were extracted and pooled in order to calculate descriptive weighted averages. Articles were evaluated on their level of evidence. A total of 20 papers were obtained, resulting in a cohort of 815 patients who were treated with hyperbaric oxygen therapy for radiation cystitis. Overall and complete response rates varied from 64.8% to 100% and 20% to 100%, respectively. The weighted average overall and complete response rates were 87.3% and 65.3%, respectively. Adverse events were observed in 9.6% of the patients, but permanent side‐effects were rare. The most prominent limitations were high cost and low availability. Hyperbaric oxygen therapy is effective in the treatment of radiation‐induced cystitis, with minimal adverse events, but low availability and high cost. At present, evidence is low; therefore, more prospective studies are required.